Islamic Spiritual Education in the Tradition of Bapalas Bidan In Banjar Tribe, Indonesia - Harisuddin, Ahmad (Dinamika Ilmu: Jurnal Pendidikan, 2021)
The multidimensional crisis that encourages the importance of developing a spiritual education model based on ethnopedagogy is the background of this research. The goal is to find the content of Islamic spiritual education in the tradition of bapalas bidan or batapung tawar, which is a rite of passage for the early life stage of the Banjar tribe. This qualitative research used an ethnometodological design in the Banjar Hulu and Banjar Batang Banyu areas represented by Hulu Sungai Selatan and Tapin Districts, with criteria-based subjects, combined quouta types and comparisons between cases. Data were collected by engaging observation and in-depth interviews; analyzed by modification of Spradley's cyclic model, which checked its validity according to the degree of trust, transferability, dependence, and certainty. This study found that the tradition of bapalas bidan can be categorized as a form of spiritual education based on the religion of Islam. At a philosophical level, this tradition symbolizes the trilogical relationship: God-man-nature through a process of meaning in the form of tabarruk and tafÃ¢'ul towards the ideal Banjar personality, namely baiman, bauntung, and batuah. Psychologically, this tradition is an expression of gratitude and moral responsibility to prepare an initial environment that is conducive to human spiritual development. As for theoretical education, this tradition describes the transfer of knowledge and spiritual transfer of values which is supported by the findings of neuroscience so that it can be reconstructed in ethnopedagogy-based learning models.